Effects of combined sildenafil-nitric oxide donor on defibrillation efficacy - Krekwit Shinlapawittayatorn (2018)
Background: A previous study demonstrated that supra-therapeutic concentration of sildenafil citrate attenuates defibrillation efficacy. However, the effect of combined sildenafil and NTG administration on defibrillation efficacy is not known. Objective: The present study investigated whether sildenafil administration at the therapeutic level increases the defibrillation threshold (DFT) when combined with NTG. Material and Method: Twenty-four pigs (20-25 kg) were randomized into four groups. After the control DFT was obtained, a stock solution of 50-mg (group 1, therapeutic concentration) and 100-mg (group 2, supra-therapeutic concentration) of sildenafil, and 100-mL of saline (groups 3 and 4) were infused at 2 mL/min. Then, NTG was administered in groups 1-3 at 5 □g/min, with an increment of 5 □g/min every 5 min. The DFT was determined again after NTG was infused for 20 minutes. Results: In group 1, the DFT (402 ± 33V, 11 ± 2J) was not different from the control (404 ± 28V, 11 ± 2J). In group 2, the DFT (521 ± 18V, 19 ± 1J) was higher (p < 0.004) than that in the control group (444 ± 31V, 14 ± 2J). Saline did not alter the DFT, either individually or in combination with NTG. Conclusion: Supratherapeutic dose of sildenafil-NTG combination significantly increased the DFT (17% of peak voltage, 37% of total energy). This effect on DFT appears to be driven by sildenafil and not NTG.